A psychometric appraisal of a revised preparedness for medication administration questionnaire in final-year undergraduate nursing students: a secondary analysis - Susan Irvine; Sharon Andrew; Christina Aggar; Nicola Whiteing; Anecita Gigi Lim; Brett Williams (BMC Nursing)
Abstract Background Students must be prepared for the transference of medication administration (pharmacology knowledge and clinical skills) to clinical practice. The Preparedness for Medication Oral Administration questionnaire has been used in several studies and demonstrated strong internal reliability and consistency. The questionnaire has been revised to align with updated medication competencies. The factor structure or dimensionality of the questionnaires has not been examined. Aim To examine the psychometric properties of the Preparedness for Medication Administration (Revised) Questionnaire. Method Data from a previous study were used to determine the psychometric properties of the Preparedness for Medication Administration (Revised) Questionnaire. Three new items were added to the revised questionnaire, and the focus shifted from the oral route of medication administration. An exploratory factor analysis was conducted to assess the reliability and dimensionality of the revised questionnaire, using principal axis factoring and Oblique rotation on the 20 items. Results Two hundred fourteen final-year undergraduate nursing students completed the questionnaire; the Kaiser–Meyer–Olkin measure confirmed sampling adequacy (.96) and Bartlett's test of sphericity χ2(214) 3003.534 p < .001 adequate sample size-to-variable ratio and inspection of the correlation matrix for loadings > 0.30. The 20 items produced a 2-factor solution, which was also confirmed by parallel analysis, with the deletion of 4 items not meeting item loadings of > 0.4. The final revised version of the questionnaire titled the Preparedness for Medication Administration Revision2 (PMAR2) contained 16 items loading onto one of the 2 factors titled Clinical Reasoning and Confidence to Practice Safely. Cronbach alpha coefficients for the factors were .89 to .95, respectively. Conclusion This research provides information for a psychometrically sound tool to assess students' preparedness for medication administration once they graduate and become independent practitioners.